Pengaruh Kualitas Layanan, Kepuasan Pelanggan Dan Promosi Di Instagram Terhadap Loyalitas Pelanggan Melalui Kepercayaan Di Layanan Spaylater - Saputra, Yogi Aska; Jatmiko, Jatmiko; Sofyan, Joel Faruk (Jurnal Ilmiah Wahana Pendidikan, 2024)
The rapid advancement of technology globally makes internet users not surprised about marketing on social media sites. Marketing power carried out with internet media is often referred to as digital marketing. The trend of digital marketing through social media, one of which is Instagram, makes it easy for companies to promote goods and services they want to trade. The purpose of this study was to examine the effect of service quality, customer satisfaction and promotions on Instagram on customer loyalty by mediating trust. Sampling was carried out using a non-probability method with a purposive sampling technique. The number of samples was determined by the method of (Hair et al., (2010) obtained 100 respondents. Data analysis used PLS-SEM as a measurement tool. Researchers obtain research results that can be used as the purpose of this study. This research hypothesis can prove that service quality, customer satisfaction, and promotions on Instagram have a direct, positive influence on trust. Next is the service quality variable, trust has a direct positive effect on customer loyalty, while customer satisfaction and promotions on Instagram do not answer the direct hypothesis on customer loyalty. The role of trust as an intervening variable can mediate the indirect effect of service quality, customer satisfaction and promotion on Instagram on customer loyalty.